Human and environmental security : an agenda for change - Dodds, Felix; Pippard, Tim (Earthscan, 2005)
'Through the lens of security the authors explore a wide range of threats and opportunities to attaining a sustainable future. Implicitly they ask: What kind of world do we want and how do we achieve it? One answer lies in the opportunity to put the politics of polarization aside and be the architects of a global participatory process. Surely that is a vision for which to strive' Elizabeth Dowdeswell President Nuclear Waste Management Organization and former Executive Director of the United Nations Environment Programme 'A highly significant and relevant publication. The authors describe in ad.